Cognitive Innovativeness and Decision-Making Styles in Iranian Shopping - Nasiri Zarandi, Hossein; Lotfizadeh, Fereshteh (British Journal of Marketing Studies, 2017)
Cognitive innovative consumers are an important segment of market for many firms, the revenues from sale of new products to these consumers and advertising by them, play an important role for firms. Hence having a correct understanding from their shopping style helps the firms to create and implement effective marketing plans for the new products. The current study investigates the shopping styles of cognitive innovative consumers. A structural equation model is used to test the relationship between cognitive innovativeness and various shopping approaches. The research is based on a sample of university student consumers in Iran. Generalizability of the results would depend on future research conducted in other cultures and consumers of other groups. The resulted findings from this research show that the shopping style of these consumers follows the quality consciousness style. Results point that firms should target the cognitive innovative customers in order to have a successful marketing in regards with attracting customers and increasing the revenues from selling their products